REFERENCE UNITS FOR CHILDREN WITH GLUTENOMIES (Scientific journal of the Fergana State University, 2024)
In this article, the expression of the thematic classification of reference units used for children with glutonyms is studied. It is explained that references to children are sometimes expressed by glutonyms, and in some cases these units are used as descriptors of the main references and acquire an attributive character.